Down the Rabbit Hole: Comment on Sundstrom and Walker (2021). Issue 3 (July 2022) - Francis, Julie; Loendorf, Lawrence L.; Kornfeld, Marcel; Larson, Mary Lou; Adovasio, James M.
Abstract : The Sheep Mountain juniper bark net, originally thought to be of Paleoindian age, was redated by Sundstrom and Walker (2021 ) to the Late Prehistoric period. Although the original investigators convincingly argued that the net was intended for use with mountain sheep or deer, Sundstrom and Walker suggest it was used to trap small game such as rabbits or sage grouse. Unfortunately, the authors ignore important information presented by the original investigators and misrepresent the archaeological record of the immediate area. The Sheep Mountain net is still best interpreted as designed for use to trap mountain sheep and deer.